2017
DOI: 10.5539/jas.v9n5p217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Management on the Physical Attributes of a Dystrophic Yellow Latosol

Abstract: Soil use and management systems aim to create conditions that are favorable to crop growth. The hypothesis is that areas subject to intensive use of agricultural machinery and animal trampling tend to have a soil structure that is altered by aggregate fragmentation, which causes soil compaction and consequently decreases the soil's physical and hydraulic properties. The aim of this study was to assess and compare the physical and hydraulic parameters of a dystrophic yellow latosol in an area of Cerrado in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This might have been caused by intense machinery traffic. These findings corroborate those of Farias et al (2017), who verified resistance to penetration increases due to changes in soil structure at surface and subterranean layers. In other words, this can be related to aggregation changes in the soil, which is mechanically fragmented by its excessive use, thus resulting in soil densification and compaction.…”
Section: Soil Resistance To Penetration Retention Curve Physical Ansupporting
confidence: 91%
See 3 more Smart Citations
“…This might have been caused by intense machinery traffic. These findings corroborate those of Farias et al (2017), who verified resistance to penetration increases due to changes in soil structure at surface and subterranean layers. In other words, this can be related to aggregation changes in the soil, which is mechanically fragmented by its excessive use, thus resulting in soil densification and compaction.…”
Section: Soil Resistance To Penetration Retention Curve Physical Ansupporting
confidence: 91%
“…Therefore, soil properties were affected and water contents in samples of the different applied potentials reduced. By contrast, Farias et al (2017) found that soil horizons with the same textural class do not always present similar curves. Thus, soil textural class influence should also be considered.…”
Section: Management Systemmentioning
confidence: 70%
See 2 more Smart Citations
“…The impacts can be summarized as changes in the macroporosity Wendling et al, 2012); aggregates stability (Fontenele et al, 2009;Santos et al, 2012;Servadio et al, 2016); organic matter content (Pragana et al, 2012;Santos et al, 2012); soil-water infiltration, aeration and permeability (Fontana et al, 2016;Farias et al, 2017).…”
Section: Introductionmentioning
confidence: 99%